Perancangan Sistem Informasi Pendaftaran Pasien Menggunakan Bahasa Pemrograman Visual Basic Pada Puskesmas Pelabuhan Sambas Sibolga - Nengsih, Yeyi Gusla; Sitorus, Mei Sryendang; Hutasoit, Theresia; Tanjung, Hizraini (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
The patient information system at the community health center is an information system that has activities such as queuing, registration and medical records. Registration services that are still manual make registration ineffective and inefficient. Officers needed a lot of time to search for documents and take notes and there was a buildup of patient queues at the registration unit. Apart from that, the manual system for making reports is not effective, so to improve registration services for patients, a health center information system is needed that is able to provide good and fast service to patients. The aim of this research is to design a registration information system application to assist registration officers in providing patient registration services. Data collection methods consist of observation methods, interview methods and documentation methods. This research approach is the SDLC (System Development Life Cycle) approach, which is a cycle used in creating or developing information systems that aims to solve problems effectively. The results obtained from this research are the design of a patient registration information system using the Visual Basic programming language. The results of the interface display from the design of the Sambas Port Health Center information system are login form, main menu form, user menu, patient registration form, patient data search menu, queue menu and patient data report menu. The conclusions obtained by this information system design can help officers in the registration unit at the Community Health Center to be more effective and efficient.